Bank-Specific Factors, Regional Economy, and RDBs’ Non-Performing Loans throughout Indonesia - Aruninggar, Hesti; Rokhim, Rofikoh (University of Merdeka Malang, 2018)
Regional development was directed to achieve national targets by taking into account the potential, aspirations, and development issues in the regions. One of the inclusive work programs in Indonesian Financial Services Sector Master Plan 2015-2019 was to develop regional economic potential by strengthening the function and role of the regional development bank in supporting the regional economy. We analyzed the influence of bank-specific factors and economic conditions of the regions, where headquarters of the regional development bank (RDB) operates, on non-performing loans recorded by RDBs throughout Indonesia. The research conducted at 25 RDBs spread all over Indonesia for six years. The data used panel data regression with the Fixed Effects method due to a possibility of region and time differences. We found that bank-specific factors and local economic conditions affect non-performing loans at RDBs. This can be seen from higher bank capitalization and operational inefficiency costs which had stimulated a significant rise in non-performing loans at RDBs, while increasing bank profitability had driven non-performing loans to drop significantly. Furthermore, in the factor of regional economic conditions, gross regional domestic product and inflation in the regions had a significant effect on decreasing level of non-performing loans at RDBs throughout Indonesia. JEL Classification: E32; G21; G28; R10; R11DOI: https://doi.org/10.26905/jkdp.v22i3.2233